Effect of air pollution on hospital admissions for systemic lupus erythematosus in Bengbu, China: a time series study. (November 2019) - Zhao, C -N; Mei, Y -J; Wu, G -C; Mao, Y -M; Wu, Q; Dan, Y -L; Pan, H -F
Recently, exposure to air pollutants has been associated with the development and progression of systemic lupus erythematosus (SLE). The current study aims to evaluate the effects of air pollutants on SLE hospital admissions in Bengbu, China. We performed distributed lag non-linear model combined with quasi-Poisson generalized linear regression to assess the impacts of air pollutants on SLE admissions from 2015 to 2017. Subgroup analyses by admission status (first admission or readmission) were also evaluated. A total of 546 hospital admissions during 2015–2017 were included. For single-day lag structures, the risk effects occurred from lag 2 to lag 9 for the 75th percentile particulate matter (PM)2.5, lag 3 to lag 9 for the 80th percentile PM2.5 . For cumulative lag structures, the risk effects occurred from lag 0–5 to lag 0–14 for both 75th PM2.5 and 80th PM2.5, and no significant effect was observed for 90th PM2.5 . In addition, the adverse effects on SLE first admissions occurred from lag 0 to lag 1 for NO2, lag 1 to lag 2 for SO2 . The maximum effect of PM2.5 on SLE was 4.27 (95% confidence interval: 1.34–13.59) at lag 0–13 day, the minimum effect value was 1.12 (95% confidence interval: 1.03–1.23) at lag 9 day. These findings demonstrate that high PM2.5, NO2 and SO2 are associated with SLE hospital admissions. In addition, this study further revealed that exposure to high concentration of PM2.5 increased the risk of SLE relapse, while high levels of NO2 and SO2 increased the risk of SLE first admissions.